Meta-theoretical thinking of psychotherapist: the essence and functions - Krupelnytska, L. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
Article is devoted to meta-theoretical thinking of psychotherapist. We have proposed the term "meta-theoretical thinking of psychotherapist" to describe professional thinking that is not carried out within the separate psychotherapeutic approach with appropriate theoretical foundation and constructs, but is the thinking "above theories", independently of them.The conscious using of meta-theoretical level allows therapist thinking to be independent, complete, accurate, and realistic. Common sense, formal logic, intellectual intuition, dialectical logic and myth logic are means of meta-theoretical thinking that. At the same time they have the answers to the question "How does meta-theoretical thinking happen?" Each of these mechanisms is responsible for the functioning of certain epistemological style.The main functions of the therapist meta-theoretical thinking are 1) forming of coordinate system in which the process of nominating and verification of therapeutic hypotheses and "life theories" is possible; 2) providing the regular basis of theoretical work of the therapist and the process of cognition through reflection and normalization process of thinking; 3) enabling autonomy of organized thinking and critical attitude to the existing theories of personality and psychotherapy, as well as the adequacy of the choice of supporting the theory to actual life situation and the client personality; 4) organization of "co-thinking" with the client to perform psychotherapy research with aims of strengthen and developing the client personality, and with means of reconstruction or creation "life theories"; 5) attracting the client to the search intellectual activity that allows psychotherapy interaction to take the subject-subject form and to transform client as passive consumer of psychotherapy services into active participant in psychotherapy research.
Keywords: meta-theoretical thinking; functions; meta-theory; psychotherapist